2020
DOI: 10.1016/j.wear.2020.203457
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of rail damage using a combination of Shakedown Map and wheel-rail contact energy

Abstract: Rolling contact fatigue and wear are two key damage mechanisms that govern rail life. Although there are several different mechanisms affecting both their initiation and propagation, the trade-off between them is important and their accurate predictions can provide significant benefits when planning rail maintenance activities. Through integration with vehicle dynamics simulations, damage models based on the wheel-rail contact energy (Tγ) and Shakedown theory have often been used to predict damage. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In Refs. [428,429], the transitions of wear mode and predominant wear equations were discussed for the cases of case-hardened 20MnCr5 under cyclic line rolling contact and the rail damage respectively. Li et al [430] predicted erosion wear and lifespan of machine gun barrel under typical shooting conditions by using a slow erosion stage wear model and a thermochemical erosion stage wear model.…”
Section: Numerical Predictions Of Wear Profile and Wear Ratementioning
confidence: 99%
“…In Refs. [428,429], the transitions of wear mode and predominant wear equations were discussed for the cases of case-hardened 20MnCr5 under cyclic line rolling contact and the rail damage respectively. Li et al [430] predicted erosion wear and lifespan of machine gun barrel under typical shooting conditions by using a slow erosion stage wear model and a thermochemical erosion stage wear model.…”
Section: Numerical Predictions Of Wear Profile and Wear Ratementioning
confidence: 99%
“…In 2019, China's HSR network has had a running distance of 29,000 km, exceeding 60% of the whole world in total [1], [2]. Due to the large passenger flow and the high operating speed of train, the damage to the internal and surface of the rails has become more and more serious [3], [4], [5], which will cause irreversible harm to the rail if not treated in time [6]. Studies have shown that rail grinding can improve rail quality and extend rail life [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this project, the repair welding technique was applied to an LT5 profile wheel which was previously operated in London Underground (LUL). Since the increased timetables and further reductions in maintenance and renewal expenditures provides new challenges to their rail-wheel interface management, they have made several attempts to maximise their asset life such as introducing novel technologies to monitor defects and conducting vehicle dynamics simulation modelling to predict the damage [1][2][3][4][5] . In respect to wheel management, an extensive measurement campaign across each individual fleet was conducted to establish a preventative turning interval within each Train Maintenance Regime (TMR).…”
Section: Introductionmentioning
confidence: 99%
“…Since the increased timetables and further reductions in maintenance and renewal expenditures provides new challenges to their rail-wheel interface management, they have made several attempts to maximise their asset life such as introducing novel technologies to monitor defects and conducting vehicle dynamics simulation modelling to predict the damage. [1][2][3][4][5] In respect to wheel management, an extensive measurement campaign across each individual fleet was conducted to establish a preventative turning interval within each Train Maintenance Regime (TMR). However, while this can help to accurately plan train maintenance scheduling, more work is still required to ensure sufficient trains are available in service to cope with increased timetables at lesser life cycle costs.…”
Section: Introductionmentioning
confidence: 99%